Whole-genome characterization and phylogenetic analysis of pigeon circovirus in racing pigeons from Heilongjiang, China - Sun, Jia; Miao, Yan; Lan, Shijie; Zhao, Jingjing; Dong, Wenying; Hu, Jia; Li, Hansong; Li, Huinan; Li, Xinran; Wang, Ming; Xu, Yaru; Li, Chunqiu; et al. (Frontiers in Veterinary Science, 2026)
Pigeon circovirus (PiCV), a globally distributed pathogen, is associated with immunosuppression and high mortality in racing pigeons. Despite its endemicity in Chinese pigeon populations, molecular epidemiological data on PiCV in Northeast China remain scarce. This study reports the first complete genome sequence of PiCV isolated from racing pigeons in Heilongjiang Province. Through next-generation sequencing (NGS) for whole-genome assembly and systematic PCR-Sanger sequencing for validation, we obtained the complete 2,035-bp genome (designated HLJ2024). Homology analysis revealed nucleotide identities of 72.9–97.7% with other PiCV reference strains; notably, the cap (Capsid) protein of HLJ2024 exhibited a signature mutation (isoleucine [I]-leucine [L]) at residue 222 relative to its closest relative strain TF4/SN/2016, with predicted structural alterations proximal to this site. Phylogenetic analysis indicated that strain HLJ2024 forms an independent clade (GI) and is closely related to strains of clade GII (TF4/SN/2016, QD6/SN/2018). Recombination analysis suggested that HLJ2024 likely arose from recombination between two Chinese parental strains-GF17/GuangDong/2014 (major parent) and TY2/SN/2016 (minor parent). Our findings reveal active PiCV evolution in Northern China driven by point mutations and inter-regional recombination, providing critical insights into viral adaptability and transmission dynamics in Northeast China. These results provide a foundation for molecular epidemiology-based surveillance of PiCV in this understudied region and hold significant implications for developing targeted prevention strategies tailored to locally circulating strains.